Post Tax Reform and Corporate Effective Tax Rate: Evidence from Tunisia - Naoui, Kamel; Kasraoui, Abdelkader (International Review of Management and Marketing, 2020)
This study examines the impact of the tax reform on corporate effective tax rate (ETR) and firm-specifics in Tunisia for the post tax reform period (after the fiscal year 2014). The corporate effective tax rate is a component by major firm-specific characteristics, especially firm size, capital structure (leverage), inventory intensity, capital intensity. The ETR provides information about the tax burdens and can be used as a political instrument to boost the economic reliance. The post tax reform period reflects the impact of lower corporate tax rate on the firm characteristics. The sample consists of 112 firm-year observations from 16 listed companies in Tunis Stock Exchange (known Bourse de Tunis- BVMT) covering seven years from 2010 to 2016. Our result indicates that the tax reform had a significant impact only on the inventory variable but no significant results on the others firm characteristics for the post-tax reform period. These findings urge the Tunisian’s tax authority to reformulate the corporate tax system. Keywords: Tax Reform, Corporate Effective Tax Rate, Tunisia. JEL Classifications: G30; G32; M4 DOI: https://doi.org/10.32479/irmm.9414